An intronic variant in the CELF4 gene is associated with risk for colorectal cancer - Teerlink, Craig C.; Stevens, Jeff; Hernandez, Rolando; Facelli, Julio C.; Cannon-Albright, Lisa A. (Cancer epidemiology, 2021)
•A pedigree-based approach identified a colorectal cancer risk variant in CELF4.•The variant was replicated using a population-based approach.•RNA structure analysis predicted the variant is destabilizing to the RNA structure.•Loss of CELF4 is a previously suggested prognostic indicator of colorectal cancer. Germline predisposition variants associated with colorectal cancer (CRC) have been identified but all are not yet identified. We sought to identify the responsible predisposition germline variant in an extended high-risk CRC pedigree that exhibited evidence of linkage to the 18q12.2 region (TLOD = +2.81). DNA from two distantly related carriers of the hypothesized predisposition haplotype on 18q12.2 was sequenced to identify candidate variants. The candidate rare variants shared by the related sequenced subjects were screened in 3,094 CRC cases and 5x population-matched controls from UKBiobank to test for association. Further segregation of the variant was tested via Taqman assay in other sampled individuals in the pedigree. Analysis of whole genome sequence data for the two related hypothesized predisposition haplotype carriers, restricted to the shared haplotype boundaries, identified multiple (n = 6) rare candidate non-coding variants that were tested for association with CRC risk in UKBiobank. A rare intronic variant ofCELF4 gene, rs568643870, was significantly associated with CRC (p = 0.004, OR = 5.0), and segregated with CRC in other members of the linked pedigree. Evidence of segregation in a high-risk pedigree, case-control association in an external dataset, and identification of additional CRC-affected carriers in the linked pedigree support a role for a rareCELF4 intronic variant in CRC risk.